Scientific and technical assistance to the evaluation of the safety of calcidiol monohydrate as a novel food - European Food Safety Authority (EFSA); Dominique Turck; Harry J. McArdle; Androniki Naska; Monika Neuhäuser‐Berthold; Giovanni Passeri; Ionut Craciun; Ruth Roldán‐Torres; Silvia Valtueña Martínez (EFSA Journal)
Abstract EFSA was asked by the European Commission to provide scientific assistance with respect to the EFSA adopted scientific opinion on ‘Safety of calcidiol monohydrate produced by chemical synthesis as a novel food pursuant to Regulation (EU) 2015/2283’, including its bioavailability as a metabolite of vitamin D3 when added for nutritional purposes to food supplements. On 5 July 2023, EFSA adopted the ‘Scientific opinion on the tolerable upper intake level for vitamin D, including the derivation of a conversion factor for calcidiol monohydrate’. This opinion concerns an updated exposure assessment for vitamin D and proposes a conversion factor for calcidiol monohydrate into vitamin D3 of 2.5 for labelling purposes. In addition, in reference to the EFSA opinion on the safety of calcidiol monohydrate, the Commission had received a letter from the pharmaceutical company EirGen Pharma Ltd requesting a revision of this opinion based on new data concerning calcidiol. Based on the information and data considered in this scientific technical report, EFSA concludes that the novel food calcidiol monohydrate proposed for use in food supplements is a bioavailable source of the biologically active metabolite of vitamin D, i.e. 1,25‐dihydroxyvitamin D, that a conversion factor of 2.5 reflects the relative bioavailability of calcidiol vs vitamin D3 under the proposed conditions of use and use levels, and that it is safe under the proposed conditions of use and use levels, i.e. up to 10 μg/day for children ≥ 11 years old and adults, including pregnant and lactating women, and up to 5 μg/day for children 3–10 years of age.